Survival following salvage abdominoperineal resection for persistent and recurrent squamous cell carcinoma of the anus: do these disease categories affect survival?. (October 2016) - Severino, N. P.; Chadi, S. A.; Rosen, L.; Coiro, S.; Choman, E.; Berho, M.; Wexner, S. D.
Abstract: Aim: This study aimed to investigate the results of salvage abdominoperineal excision (APR) in patients with persistent or recurrent squamous cell carcinoma of the anus (SCCA). Method: Patients with anal neoplasia were identified from a prospective database. Patients with invasive SCCA with demonstrated failure of chemoradiation therapy (CRT) who underwent salvage APR for one of three disease categories (persistent, < 6 months post‐CRT; early recurrent, 6–24 months post‐CRT; late recurrent, > 24 months post‐CRT) were included. The primary outcome was overall survival after salvage APR. Tumour size, metastatic lymph nodes (LN), circumferential resection margin positivity (CRM) and neurolymphovascular invasion (NLVI) were correlated with the outcome. Results: Thirty‐six patients with a median 3‐year overall survival of 46% (median follow‐up 24 months) underwent salvage APR due to persistent or recurrent SCCA (14 men, mean age 59 years). Eleven (31%) patients were diagnosed with persistent disease, 17 (47%) with early and 8 (22%) with late recurrence. Two‐year overall survival of Stage 0/I/II and III/IV disease was 81.5% and 33.74%, respectively ( P = 0.022). Overall disease stage was associated with disease categorization ( P = 0.009): patients with persistent disease or early recurrence had a significantly higher disease stage than patients with late recurrence (OR = 20.9 and 17.2). Despite apparently improved survival in patients with late disease recurrence on live table analysis, no significant difference was identified in overall survival when stratified by disease category on log‐rank test analysis. Conclusion: Persistent and recurrent disease does not show any significant difference in survival, but patients with late recurrence may have a better prognosis.